2010
DOI: 10.1007/s00595-009-4151-1
|View full text |Cite
|
Sign up to set email alerts
|

Transectional gastrectomy: An old but renewed concept for early gastric cancer

Abstract: Segmental resection of the stomach was first described at the end of the 19th century by Mikulicz, who devised it to preserve the pylorus when performing gastric ulcer surgery. Although this technique was abandoned because of delayed gastric emptying, in 1967 Maki et al. developed a new improved concept of segmental gastrectomy: pylorus-preserving gastrectomy (PPG). The dramatic decrease in the occurrence of gastric ulcers limited the opportunity to perform these operations; however, PPG was then used for trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…We established function-preserving gastrectomy in combination with LBD on the basis of the favorable results of our feasibility study for the SN concept [18,36]. Functionpreserving gastrectomy for early gastric cancer includes not only transectional gastrectomy but also local resection, cardia resection, and antral resection.…”
Section: Function-preserving Gastrectomy As Snnsmentioning
confidence: 99%
“…We established function-preserving gastrectomy in combination with LBD on the basis of the favorable results of our feasibility study for the SN concept [18,36]. Functionpreserving gastrectomy for early gastric cancer includes not only transectional gastrectomy but also local resection, cardia resection, and antral resection.…”
Section: Function-preserving Gastrectomy As Snnsmentioning
confidence: 99%
“…The indication for SG for gastric cancer is limited, similar to PPG. Fujimura et al [14] proposed a new SG technique using sentinel node navigation for early cancer located in the middle third of the stomach. The results of the questionnaire survey showed that only 23 institutions (16%) performed SG.…”
Section: Segmental Gastrectomymentioning
confidence: 99%
“…Pylorus-preserving gastrectomy (PPG), including transectional resection (TR) and local resection (LR), in patients with early gastric cancer along with lymphatic basin dissection, has been found to modulate gastric emptying and prevent DGR (23,24). Moreover, sleeve gastrectomy has been reported to lead to H. pylori eradication (25).…”
Section: Introductionmentioning
confidence: 99%